Classroom Management Training for Beginner Teachers at the Raudhatul Atfal (RA) GUPPI Kalak Institution - Sanjaka Yekti (IMPACT: Journal of Innovation Mission and Community Service, 2025)
Classroom management is an important pedagogical competency that must be possessed by Early Childhood Education (PAUD) teachers, including Raudhatul Atfal (RA) teachers. Beginner teachers often face various obstacles in managing classes due to limited experience and understanding of classroom management strategies that are appropriate to the characteristics of early childhood. This community service activity aims to improve the classroom management competency of beginner teachers at the Raudhatul Atfal (RA) GUPPI Kalak Institution through a structured and applicable training program. The implementation method includes needs analysis, interactive lecture-based training, discussions, simulations, and mentoring in classroom implementation. The results of the activity show an increase in teachers' understanding of classroom management concepts, improved skills in managing children's behavior, and changes in teacher attitudes to become more confident and reflective in creating a conducive and child-friendly learning climate. This training also encourages the integration of Islamic values in RA classroom management practices. Thus, classroom management training for beginner teachers at RA GUPPI Kalak has proven effective as an effort to improve teacher pedagogical competency and the quality of PAUD learning.